Enabling New Generation Entrepreneurs in Horticulture through Horti-Business Incubation - Dinesh, M R; Prasanna, H C; Laxman, R H (Indian Farming, 2020)
Institute Technology Management Unit & Agri-Business Incubation centre located at ICAR-Indian Institute of Horticultural Research, Bengaluru is a facility of Indian Council of Agricultural Research (ICAR) created through National Agriculture Innovation Fund (NAIF) to commercialize the technologies of ICAR-IIHR by non-exclusive licensing, nurture horticulture technology based start-ups/ventures and horti-business consultancy through incubation. Technology developed for the benefit of farmers and other stakeholders will be successful when it is adopted by large number of growers. This is possible only when the technology is made available in adequate quantity with quality. The technologies developed by the research institutes was made available for farming community through commercialization and incubation of start-ups. Main objective of ITMU & ABI unit is to impart appropriate IP protection to the innovations, showcase, transfer, commercialize innovations from the ICAR-IIHR. The ITMU and ABI a unit of ICAR-IIHR, Bengaluru strives to be a bridge that links the research community with all the stakeholders of horticulture and business community. It attempts to promote horti-business ventures through technology development, dissemination and commercialization for everyone from corporate to individual farmer.